2003
DOI: 10.1088/0960-1317/13/6/307
|View full text |Cite
|
Sign up to set email alerts
|

Sodium contamination of SiO2caused by anodic bonding

Abstract: In this paper we present an investigation of sodium contamination of SiO2 (oxide) during anodic bonding. Sodium contamination can be deleterious to the electrical properties of silicon structures. Silicon wafers with metal–oxide semiconductor (MOS) capacitors were bonded to Corning 7740 (Pyrex) glass wafers. The concentration of mobile ions was measured on capacitors outside and within glass cavities using the triangular voltage sweep method. Using secondary ion mass spectrometry analysis, it was confirmed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…31 The PECVD oxide was patterned and removed from the cantilever surface before the anodic bonding to minimize bending due to the mismatch of thermal expansion. Subsequent fabrication steps are identical to those for SMRs without piezoresistive readout.…”
Section: Device Fabricationmentioning
confidence: 99%
“…31 The PECVD oxide was patterned and removed from the cantilever surface before the anodic bonding to minimize bending due to the mismatch of thermal expansion. Subsequent fabrication steps are identical to those for SMRs without piezoresistive readout.…”
Section: Device Fabricationmentioning
confidence: 99%
“…72 All of these new lithiumcontaining glasses have been reported to have successfully bonded to silicon at y200uC in the presence of a suitable electric field. [69][70][71][72] The effects of sodium contamination during anodic bonding have recently been addressed by Schjølberg-Henriksen et al 73,74 in the context of monolithically integrated MEMS in which the relevant electronics for the device to operate sit together with the device on a single chip. Using metal-oxide semiconductor (MOS) capacitors as test structures, they have demonstrated that sodium contamination can occur during anodic bonding, but that its effect can be minimised to an acceptable level by the application of a 100 nm thick protective plasma-enhanced chemical-vapour-deposited silicon nitride layer protecting the electronics.…”
Section: Glasses As Cathode Materialsmentioning
confidence: 99%
“…Using metal-oxide semiconductor (MOS) capacitors as test structures, they have demonstrated that sodium contamination can occur during anodic bonding, but that its effect can be minimised to an acceptable level by the application of a 100 nm thick protective plasma-enhanced chemical-vapour-deposited silicon nitride layer protecting the electronics. If such precautions are taken during anodic bonding, together with suitable precautions which avoid high electrical fields across sensitive electrical components, 73 the perceived incompatibility of anodic bonding with microelectronic components can be overcome. As Schjølberg-Henriksen et al 73 note, this will enable further device miniaturisation and may also lower production costs.…”
Section: Glasses As Cathode Materialsmentioning
confidence: 99%
“…1 is also effective to protect CMOS [11]. Na ion in a borosilicate glass is harmful for CMOS [12], but pn junctions are normally protected with a back-end-of-line (BEOL) layer. Therefore, this is more problematic for piezoresistors for strain sensing.…”
Section: Bonding For Hermetic Packagingmentioning
confidence: 99%